HBIM and BEM association: Systematic literature review. - Costa, Aline Prado; Cuperschmid, Ana Regina Mizrahy; Neves, Leticia Oliveira (Journal of Cultural Heritage, 2024)
• Interoperability between HBIM and BEM simulation tools is a challenge in most papers. • Graphical visualization of HBIM and BEM output data aids understanding of results. • Visual Programming Language software creates replicable simulation routines effectively. • Collecting data on buildings without damaging their structures is a major challenge. • HBIM and BEM need better integration to speed workflow and reduce data transfer. Building performance simulations are a complex process, especially when applying to buildings of historical interest. This paper proposes a Systematic Literature Review to investigate how Historic Building Information Modeling (HBIM) and Building Energy Modeling (BEM) can act as effective computational simulation tools and how their association has been practiced. The study selected 19 relevant publications from the period between 2012 and 2022 to identify the most frequently used software tools, data exchange, and input and output variables for thermal and energy simulations. The review found important research gaps, such as the need for better interoperability between HBIM and BEM simulation tools and the collection of accurate physical data on historical buildings without causing structural damage. The study highlights the need for better integration between HBIM and BEM resources to increase workflow speed and reduce the need for data transfer.